2023
DOI: 10.3390/healthcare11121756
|View full text |Cite
|
Sign up to set email alerts
|

The Right to Refuse: Understanding Healthcare Providers’ Perspectives on Patient Autonomy in Emergency Care

Ahmed M. Al-Wathinani,
Dennis G. Barten,
Hind Alsahli
et al.

Abstract: Healthcare providers in prehospital care and emergency departments are often at the frontline of medical crises, facing a range of ethical dilemmas, particularly when it comes to patients refusing treatment. This study aimed to delve into the attitudes of these providers toward treatment refusal, unearthing the strategies they employ in navigating such challenging situations while actively working in prehospital emergency health services. Our findings showed that, as the participants’ age and experience increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
0
1
Order By: Relevance
“…This discovery contrasts with some prior research, which suggested women might have higher safety awareness due to inherent empathetic tendencies [23]. The lack of empirical support for such a correlation in our study underscores the necessity for further exploration into the complex role gender plays in healthcare safety awareness [24,25].…”
Section: Discussioncontrasting
confidence: 99%
“…This discovery contrasts with some prior research, which suggested women might have higher safety awareness due to inherent empathetic tendencies [23]. The lack of empirical support for such a correlation in our study underscores the necessity for further exploration into the complex role gender plays in healthcare safety awareness [24,25].…”
Section: Discussioncontrasting
confidence: 99%